Investigating the role of chemical additives in the structure and dynamics of electrolyte mixtures via 2D infrared spectroscopy and microscopy - Tibbetts, Clara Anne, author; Krummel, Amber T., advisor; Wilson, Jesse, committee member; Levinger, Nancy, committee member; Rappe, Anthony, committee member (Colorado State University. Libraries, 2022)
The research in this dissertation is focused on the impact that additives have on the chemical structure and dynamics of electrolyte solutions that can be used in electrochemical devices such as batteries or solar devices. Two-dimensional infrared spectroscopy (2D IR) has been used in conjunction with linear Fourier Transform infrared spectroscopy (FTIR), rheology, molecular dynamics, and density functional theory to study organic carbonate and ionic liquid mixtures. In addition, 2D IR microscopy is successfully implemented to study ionic liquid mixtures in different environments including a microdroplet and a copper electrochemical cell. 2D IR and molecular dynamics simulations of organic carbonate mixtures with varied amounts of a common additive, fluoroethylene carbonate (FEC), show that even in small quantities FEC can induce changes in the solvent structure. Experimental results demonstrated that at low concentrations FEC slows spectral diffusion. Cylindrical distribution functions calculated from molecular dynamics simulations in conjunction with experimental results suggest the slowing is due to significant changes in the behavior of one of the solution components, ethylene carbonate. Furthermore, a combination of experimental anisotropy and viscosity, and computational rotational correlation functions shows that local solvent rigidity increases with high amounts of FEC. Moreover, these results show that additional FEC increases macroscopic viscosity which is correlated to global solvent orientational relaxation. In functional batteries FEC is shown to dramatically impact how the solid electrolyte interphase forms, a layer that impacts battery metrics such as lifetime and safety.1–3 Therefore, it is possible that the observed changes in the solvent structure upon addition of FEC has implications in how the solid electrolyte interphase forms. The combination of linear and 2D IR spectroscopy with viscosity measurements is used to study the impact of small amounts of water (between ~1.32 and 21.6% mole fraction water) on the structure and dynamics of room-temperature ionic liquid mixtures. Specifically, the effects of water on a mixture of 1-butyl-3-methylimidazolium tetrafluoroborate (BmimBF4) and 1-butyl-3-methylimidazolium dicyanamide (BmimDCA) room-temperature ionic liquid (RTIL) was investigated by tracking changes in the vibrational features of the dicyanamide anion (DCA). Shifts in the infrared peak frequencies of DCA indicated the formation of water-associated and non-water-associated DCA populations. Time-dependent 2D IR shows differences in the dynamic behavior of the water-associated and non-water-associated populations of DCA at low (below 2.5% χWater), mid (between 2.5% χWater and 9.6% χWater), and high (between 11.6% χWater and 21.6% χWater) water concentrations. The vibrational relaxation occurs more quickly with increasing water content for water-associated populations of DCA, indicating water introduces additional pathways for relaxation, possibly via new bath modes. On the other hand, spectral diffusion of water-associated populations slows significantly with more water, suggesting water induces the formation of distinct and non- or very slowly interchangeable local environments. It is possible that in a functional electrochemical device with a water and RTIL electrolyte the introduction of these diverse local solvent environments might impact device performance. If water could be introduced in a system in a way that increased ion-mobility but does not cause undesirable interfacial interactions near an electrode this could improve device efficiency. Therefore, determining if and how this local heterogeneity presents itself in an operational electrochemical cell is an important next step. Ultrafast 2D IR microscopy is discussed as an emerging imaging platform that is a promising tool for investigating heterogeneous samples across multiple time scales and length scales, including electrochemical devices. However, there are numerous practical considerations in the implementation of 2D IR microscopy. Some of these considerations include mid-IR laser sources, repetition rates, mid-IR pulse shaping, noise reduction, microscope design, and detection limitations. In this work we show the implementation of improvements in spectral resolution and noise reduction and the consequent successful imaging of a BmimDCA:BmimBF4 electrolyte in two different scenarios—a droplet and a copper electrochemical cell. Imaging the BmimDCA:BmimBF4 microdroplet shows how 2D IR imaging can be used to probe dynamics on a spatial scale. Results indicate the solvent dynamics in the microdroplet are spatially homogenous. Imaging experiments of the RTIL electrolyte in a copper cell, demonstrates a practical application of ultrafast 2D IR microscopy to study functional electrochemical devices. 2D IR spectra collected between the copper counter electrode and working electrode showed dramatic changes in peak positions and shapes suggesting the formation of DCA copper complexes. These results suggest 2D IR microscopy will allow chemical exchange dynamics of different species involved in the electrochemical reactions to be monitored as they evolve from the counter electrode to the working electrode. This work establishes 2D IR microscopy as a tool well equipped to connect molecular level condensed phase reaction dynamics to micro- and mesoscale spatial dependence in an electrochemical cell.
Keywords: additives; imaging; organic carbonates; electrolytes; 2D infrared spectroscopy; ionic liquids